Viabilidade econômica da utilização agrícola do biossólido da Unidade de Gerenciamento de Lodo (UGL) Ouro Verde - Marcon, Mônica Kristina Foltran (2014)
Due to the growing global demand for food production and energy crops that are directly related to increased use of fertilizers, the use of viable alternatives for economic and environmental way, go against the concept of sustainability in order to avoid the risk shortages and rising prices of the product. The residue from the treatment of sewage, known as sludge, can be used as provided met the requirements laid down by Resolution CONAMA 375/2006. Agricultural recycling of sewage sludge as a fertilizer, is permitted for crops whose edible portion does not contact with the soil, being forbidden to vegetable crops, tubers, roots and flooded crops. From data Sanitation Company of Paraná (SANEPAR), where found reports of analyzes of agronomic parameters of ten (10) batches of biosolids processed in Sludge Management Unit (SMU) Green Gold, the city of Foz do Iguaçu . For each batch were related concentrations of N, P, K, Ca and Mg entered into biosolids. Assuming that the sludge is donated to registered farmers in the sanitation company, which, however, are responsible for transportation costs and that this expenditure is only advantageous if it is equivalent to the cost of fertilizers available in the market, the price was determined fertilizer per batch of biosolids in order to establish the maximum distance that justifies the search and replacement of chemical fertilizer by biosolids. The main findings conclude that in a ton of biosolids SMU Green Gold are inserted from R$ 30.83 to R$ 167.32 fertilizers, considering the worst and the best scenario, respectively. Thus, the compensatory distance search of biosolids to farmers ranged from 280.24 km to 1521.12 km. Reducing the damp content of the biosolids allows more nutrients to be transported. Agricultural recycling of sewage sludge from SMU Gold Green allows the reduction of dependence on fossil fuels for the production of chemical fertilizer NPK at 362.81 MJ.kg-1, considering the sludge on a dry basis.